2022
DOI: 10.1002/masy.202100458
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on the Influence of Nanosilica‐Reinforced Epoxy Resin on the Delamination Behavior of Composite Laminates

Abstract: The use of nanomodified epoxy resins can potentially increase composites application to aeronautical structural components, thanks to the potential enhancement, in terms of physical and mechanical properties, when compared to the neat epoxy matrix. In this work, the effects of silica nanoparticles (NPs) on the fracture toughness and, consequently, the crack growth resistance of fiber-reinforced polymers (FRPs) have been numerically investigated. The skin-stringer debonding initiation and growth have been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The incorporation of nanomaterials (carbon nanotubes (CNTs), graphene, nanoclay, nanosilica, and so forth) into composites to form nano-engineered composites has been investigated in the literature with the aim of improving their strength, [1,2] stiffness, [3] fracture toughness, [4] and fatigue properties. [5,6] Since the synthesis of CNTs in the 1990s, [7] this type of nanomaterial has been widely investigated due to its excellent mechanical properties, as well as its high thermal [8] and electrical conductivity. [9] In the literature, a noticeable enhancement in the thermal conductivity of resin-CNTs samples has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of nanomaterials (carbon nanotubes (CNTs), graphene, nanoclay, nanosilica, and so forth) into composites to form nano-engineered composites has been investigated in the literature with the aim of improving their strength, [1,2] stiffness, [3] fracture toughness, [4] and fatigue properties. [5,6] Since the synthesis of CNTs in the 1990s, [7] this type of nanomaterial has been widely investigated due to its excellent mechanical properties, as well as its high thermal [8] and electrical conductivity. [9] In the literature, a noticeable enhancement in the thermal conductivity of resin-CNTs samples has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Because the tensile radial stress is mainly caused by the thermal expansion coefficient (CTE) mismatch between the REBCO CC and the epoxy resin layer in the epoxy impregnated REBCO pancake coil. In this regard, the investigation showed that the thermal stress can be reduced by modifying the CTE of the epoxy resin by adding fillers to the epoxy resin [38][39][40][41]. Meanwhile, the overband fabrication technology is also widely used in the epoxy impregnated REBCO pancake coil or no-insulation REBCO coil to reduce the radial and hoop stresses [42][43][44].…”
Section: Introductionmentioning
confidence: 99%